A STUDY ON MORPHOMETRIC, HAEMATOLOGICAL, AND FEEDING ANALYSIS OF BAYA WEAVER (PLOCEUS PHILIPPINUS) FROM PAKISTAN - Warda Zafar; Muhammad Waseem Aslam; Ahmad Waheed; Ali Umar; Nazaket Ali; Tehmina Khan; Rida Tahir; Azka Zafar; Muhammad Shoaib Sharif; Muhammad Wajid; Muhammad Saleem Khan; Muhammad Ahmad (Journal of Animal and Plant Sciences, 2023)
Baya weaver is found in floodplains of Pakistan and is famous for building retort shaped hanging nests. For this study, 24 samples of baya weaver (twelve from both sexes) were collected from the wild habitat to analyze morphometry, haematology, and gut contents. Morphometric parameters e.g., body weight was measured with the help of a weight balance while body weight, body length, tail length, wingspan, wing length, longest primary feather, tarsus, central toe length, head length with and without bill, bill length, and chest circumference were measured with measuring tape. Feeding analysis was carried out through a study of complete gastrointestinal tracts (GITs). For that purpose, birds were anaesthetized with a combination of ketamine HCL (10 mg/kg) and diazepam (0.2 mg/kg). GITs were removed through dissection and kept in 10% formalin and analyzed in an ornithological lab with the help of dissecting microscopes. About 5 μL blood was taken from the wing vein and stored in the EDTA tube for haematological analysis. The body length (male 18.43±0.58cm, 15.93±0.26cm) and chest circumference (male 12.53±0.05 cm, female 12.00±0.22 cm) of both sexes were significantly different between male and female baya weavers. Both sexes mostly feed on wheat and rice. However, pin red grass (Saccharum munja), beetles, moths, sunflower seeds, and plant materials were also recorded in the study. Haematological parameters were recorded for the first time for baya weaver in this study. This study concludes that male baya weaver has a longer body length and chest circumference as compared to female baya weaver. The preferred food of male baya weaver was beetles, while female’s preferred food was rice.
Keywords: Baya weaver; Haematology; Feeding; Morphometric parameters